HOW DOES REMOTE WORKING ENHANCE FLOW EXPERIENCE? THE ROLE OF EMPLOYEES' PSYCHOLOGICAL WELL-BEING - Demirhan, Ayse; Bulgur, Nazli Ece (RESEARCH CENTER PUBLIC ADM & PUBLIC SERVICE, 2023)
The main purpose of this research was to explore the moderating role of psychological well-being in the relationship between remote working and flow. Based on that, a survey was conducted on 238 managers and administrative staff who are working in the IT industry, Telecommunications industry, Retail industry and Banking sector in Istanbul, Turkey. Remote working scale developed by Grant has been used to measure e-working (17 statements). Flow scale developed by Bakker has been used to measure the flow, a scale consisting of 13 statements. The scale developed by Diener, Scollon & Lucas and adapted to Turkish version by Telef was used to measure the level of psychological well-being (8 items). According to the results of the analysis, there is a relationship between remote working and flow. Also, it was revealed that psychological well-being has a mediating role between remote working and flow. The value of this study consist in highlighting the related aspects concerning remote working and flow experience of Turkish employees working in the IT industry, Telecommunications industry, Retail industry and Banking sector and their psychological wellbeing levels.
Keywords: Remote Working; Flow Experience; Psychological Well-Being; POSITIVE EMOTIONS; HAPPINESS; MODEL; Business & Economics